Citizen engagement on Spanish political parties’ Facebook pages: Analysis of the 2015 electoral campaign comments (Communication & Society, 2017)
Political parties’ use of social networks to spread their messages allows for citizen engagement and fosters debate among social networks users. In this paper, we analyze said engagement in the comments written by citizens on the Facebook pages of the major Spanish political parties during the 2015 general election campaign. We describe the characteristics of citizen engagement in a political context and determine if there are any differences amongst the comments published on the political parties’ pages. We employ a two-phase quantitative methodology. First, we analyze the distribution of the 68,747 citizen comments posted on the profiles of PP, PSOE, Podemos, and Ciudadanos, based on the level of engagement and which party’s page they appear on. Second, we perform a computerized content analysis of the comments to identity the most used words, the emotional valence of the messages, and the type of language citizens use to interact with one another. The results indicate that users associated with the new parties engage in such ways that differ from those users associated with the traditional parties. Moreover, interaction among users of these platforms is characterized by disagreement and more negative, offensive language, especially on the Facebook pages of the most ideologically polarized parties